Assessment of timber and fuel wood harvesting practices and distribution pattern in CFUGs of Khotang District, Nepal - Kushmi, Leera; Ojha, Narendra; Khadka, Shiva (Journal of Forests, 2024)
Proper harvesting of forest products is necessary for sustainable forest management, playing a pivotal role in minimizing damage and waste while ensuring the sustainability of forest resources. Sustainable community forest management greatly depends on the harvesting and fair distribution of various forest products (FP). The study's goals were to ascertain the methods, instruments, and strategies utilized in the harvesting process, forest products distribution pattern, and the common issues surrounding the distribution and harvesting of FP in Imo and Ashoje Community Forest (CF) located in Khotang District, Nepal. Operational Plan (OP), focus groups, key informant interviews, household surveys, and minute books were used for data collection. 25% of all households were chosen at random from each of the two CF. The study revealed that traditional methods and tools such as sickles, bill hooks, axes, and saws, were commonly used in the past; however, there has been a shift towards modern tools in recent years. Deviations were observed in forest products harvesting and distribution from that of OP in practice. Fuel wood were equally distributed, timbers were allocated based on priority and circular basis ensuring user satisfaction. The slope was the major constraint for harvesting, as most of the marked trees were not cut because of difficulty in extraction. To improve sustainable forest management, it is recommended that advanced tools and training be provided to users, with regular monitoring by forest officials to ensure adherence to best practices. These measures will help enhance user responsibility and ensure sustainable harvesting operations.